Hydrodynamic control of cadmium retention and bioaccumulation in a temperate estuary - Vibe Schourup-Kristensen; Janus Larsen; Martin M. Larsen; Jakob Strand; Lily-Jade Dupont; Ane Lopez de Gamiz Zearra; Gaia Grieco; Zhanna Tairova; Lindsey J. Broadus; Charlotte H. Clubley; Ange P. Ishimwe; Jesper Philip Aagaard Christensen; et al. (Marine Pollution Bulletin, 2026)

RGD-Alginate beads as scaffolds for culturing primary human dermal and pulmonary fibroblasts - M.C. Stahl; K.G. Bergendahl; D. Zaytseva-Zotova; K.R. Rytterager; C.T. Nordgård; J.S. Kjesbu; H. Haslene-Hox; Ø. Halaas; P. Sætrom; A.S. Chahal; B.L. Strand (Carbohydrate Polymers, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

The gut microbiome differs between hygiene-performing and non-hygiene-performing worker honey bees - Y. H. Tola; K. Wagoner; M. K. Strand; O. Rueppell; D. R. Tarpy (Insectes Sociaux, 2025)
Gut microbiomes play a significant role in the health, development, and behavior of numerous species, including honey bees ( Apis mellifera ). Worker honey bees exhibit varying degrees of hygienic behavior, which involves the removal of unhealthy brood to mitigate disease within their colony. However, the potential relationship between hygienic behavior and the honey bee gut microbiome has not been previously investigated. In this study, we compared gut microbiota in honey bees engaged in hygienic behavior (hygiene performers) versus those not exhibiting this behavior (non-hygiene performers) using 16S rRNA gene amplicon sequencing. Proteobacteria, Firmicutes, and Actinobacteria were identified as the predominant phyla. Notably, three bacterial species ( Apilactobacillus kunkeei , Bartonella apis, and Frischella perrara ) were found to be more abundant in hygiene performer bees compared to non-hygiene performer bees. Additionally, hygiene performer bees showed a higher diversity of amplicon sequence variants, with Apibacter mensalis being exclusively present in hygiene performer bees and absent in non-hygiene performer bees. These findings reveal an association between gut microbiota composition and hygienic behavior in honey bees, which may provide a foundation for future research exploring probiotic development and other strategies to enhance honey bee health.

Tracking rapid ice recession in a major Southern Alps valley during the last glacial termination - Peter D. Strand; Aaron E. Putnam; Joerg M. Schaefer; George H. Denton; David J.A. Barrell (Quaternary Science Reviews, 2024)

On the short-term response of entrained air bubbles in the upper ocean: a case study in the north Adriatic Sea - Alvise Benetazzo; Trygve Halsne; Øyvind Breivik; Kjersti Opstad Strand; Adrian H. Callaghan; Francesco Barbariol; Silvio Davison; Filippo Bergamasco; Cristobal Molina; Mauro Bastianini (Ocean Science, 2024)
Air bubbles in the upper ocean are generated mainly by waves breaking at the air–sea interface. As such, after the waves break, entrained air bubbles evolve in the form of plumes in the turbulent flow, exchange gas with the surrounding water, and may eventually rise to the surface. To shed light on the short-term response of entrained bubbles in different stormy conditions and to assess the link between bubble plume penetration depth, mechanical and thermal forcings, and the air–sea transfer velocity of CO2, a field experiment was conducted from an oceanographic research tower in the north Adriatic Sea. Air bubble plumes were observed using high-resolution echosounder data from an upward-looking 1000 kHz sonar. The backscatter signal strength was sampled at a high resolution, 0.5 s in time and 2.5 cm along the vertical direction. Time series profiles of the bubble plume depth were established using a variable threshold procedure applied to the backscatter strength. The data show the occurrence of bubbles organized into vertical plume-like structures, drawn downwards by wave-generated turbulence and other near-surface circulations, and reaching the seabed at 17 m depth under strong forcing. We verify that bubble plumes adapt rapidly to wind and wave conditions and have depths that scale approximately linearly with wind speed. Scaling with the wind–wave Reynolds number is also proposed to account for the sea-state severity in the plume depth prediction. Results show a correlation between measured bubble depths and theoretical air–sea CO2 transfer velocity parametrized with wind-only and wind/wave formulations. Further, our measurements corroborate previous results suggesting that the sinking of newly formed cold-water masses helps bring bubbles to greater depths than those reached in stable conditions for the water column. The temperature difference between air and sea seems sufficient for describing this intensification at the leading order of magnitude. The results presented in this study are relevant for air–sea interaction studies and pave the way for progress in CO2 gas exchange formulations.

Fine-scale spatial variation of northern shrimp and Atlantic cod across three Norwegian fjord systems and implications for management - Fabian Zimmermann; Jessica Tengvall; Hans Kristian Strand; Kjell Nedreaas; Trude H. Thangstad; Berengere Husson; Guldborg Søvik (Estuarine, Coastal and Shelf Science, 2023)

Two invasive Hieracium species’ potential distributions within the Greater Yellowstone Ecosystem were defined using invasion susceptibility models and habitat typing - Christie H. Guetling; Lisa C. Jones; Eva K. Strand; Don W. Morishita; Julia Piaskowski; Timothy S. Prather (Biological Invasions, 2023)
Invasive Hieracium plant species are invading the Greater Yellowstone Ecosystem. The potential distribution of orange hawkweed ( Hieracium aurantiacum) and meadow hawkweed ( Hieracium caespitosum) were estimated using habitat susceptibility models to assist land managers’ management of these invasive plants. The objectives of this study were to: (1) develop models describing susceptibility of ecosystems to hawkweed invasion, (2) identify indicator species of orange hawkweed and meadow hawkweed, (3) determine habitat types where these invasive hawkweeds might occur, and (4) create habitat susceptibility maps for management planning and ground surveys. Models were developed using a Mahalanobis distance similarity technique from remotely sensed biotic and abiotic variables, as well as known location data for orange and meadow hawkweed. Ground validation was conducted to assess model weaknesses and subsequent model modification. Indicator plant species were identified as surrogates to determine the likelihood of hawkweed presence during ground survey. Transect data collected from areas susceptible to invasion also were used to determine habitat types where hawkweed might occur. The best model included eight variables: north–south aspect, east–west aspect, slope, NDVI, NDWI, blue spectral band, green spectral band, and precipitation. High susceptibility (65 + % likelihood of suitable habitat) consisted of 66,000 ha for meadow hawkweed and 35,000 ha for orange hawkweed, 5.0% and 2.7% of the study area, respectively. Meadow hawkweed and orange hawkweed had seven and three indicator plant species, respectively. Predicted hawkweed habitat susceptibility encompassed nine habitat types, ranging from xeric sagebrush steppe to wet forests and they overlapped except at the xeric habitat type. Habitat susceptibility models save costs and allow survey prioritization to those areas most susceptible to invasion.

An aphid symbiont confers protection against a specialized RNA virus, another increases vulnerability to the same pathogen - Clesson H. V. Higashi; William L. Nichols; Germain Chevignon; Vilas Patel; Suzanne E. Allison; Kyungsun Lee Kim; Michael R. Strand; Kerry M. Oliver (Molecular Ecology, 2023)
Insects often harbour heritable symbionts that provide defence against specialized natural enemies, yet little is known about symbiont protection when hosts face simultaneous threats. In pea aphids ( Acyrthosiphon pisum ), the facultative endosymbiont Hamiltonella defensa confers protection against the parasitoid, Aphidius ervi , and Regiella insecticola protects against aphid‐specific fungal pathogens, including Pandora neoaphidis . Here, we investigated whether these two common aphid symbionts protect against a specialized virus A . pisum virus (APV), and whether their antifungal and antiparasitoid services are impacted by APV infection. We found that APV imposed large fitness costs on symbiont‐free aphids and these costs were elevated in aphids also housing H . defensa . In contrast, APV titres were significantly reduced and costs to APV infection were largely eliminated in aphids with R . insecticola . To our knowledge, R . insecticola is the first aphid symbiont shown to protect against a viral pathogen, and only the second arthropod symbiont reported to do so. In contrast, APV infection did not impact the protective services of either R . insecticola or H . defensa . To better understand APV biology, we produced five genomes and examined transmission routes. We found that moderate rates of vertical transmission, combined with horizontal transfer through food plants, were the major route of APV spread, although lateral transfer by parasitoids also occurred. Transmission was unaffected by facultative symbionts. In summary, the presence and species identity of facultative symbionts resulted in highly divergent outcomes for aphids infected with APV, while not impacting defensive services that target other enemies. These findings add to the diverse phenotypes conferred by aphid symbionts, and to the growing body of work highlighting extensive variation in symbiont‐mediated interactions.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Ice-confined construction of a large basaltic volcano—Austurfjöll massif, Askja, Iceland - A. H. Graettinger; D. W. McGarvie; I. P. Skilling; A. H. Höskuldsson; K. Strand (Bulletin of Volcanology, 2019)

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Photoperiod revisited: is there a critical day length for triggering a complete parr–smolt transformation in Atlantic salmon Salmo salar ? - Jo E. T. Strand; David Hazlerigg; Even H. Jørgensen (Journal of Fish Biology, 2018)
The present study investigated whether there is a critical length of photoperiod needed to stimulate a completed parr–smolt transformation (PST) in Atlantic salmon Salmo salar . In two experiments, S. salar parr of the Norwegian aquaculture strain held on continuous light were exposed to a short photoperiod (6 L:18D) followed by exposure to 8 L:16D, 12 L:12D, 16 L:8D, 20 L:4D and 24 L:0D in experiment 1 or to 6 L:18D followed by maintenance on 6 L:18D or exposure to 12 L:12D and 24 L:0D photoperiods in experiment 2. All groups, irrespective of photoperiod treatment, developed improved hypo‐osmoregulatory ability. However, the development was greatest in the groups exposed to 20 L:4D and 24 L:0D in experiment 1 and 24 L:0D in experiment 2. In experiment 2, gill Na + – K + ‐ATPase activity increased in the group exposed to 24 L:0D, but not in the groups exposed to 12 L:12D and 6 L:18D. The groups exposed to 20 L:4D and 24 L:0D in experiment 1 and 24 L:0D in experiment 2 also grew better than fish exposed to shorter photoperiods. In experiment 2 only the group exposed to 24 L:0D showed a decrease in condition factor and increases in plasma growth hormone and brain type 2 deiodinase mRNA abundance. Hence, only the groups exposed to photoperiods above 16 L:8D developed classical smolt indices in the present experiment, leading us to conclude that the photoperiod increase needs to exceed 16 h daylight for stimulating a complete PST in the S. salar used in the present study.

The histone deacetylases HDAC1 and HDAC2 are required for the growth and survival of renal carcinoma cells - Nicole Kiweler; Boris Brill; Matthias Wirth; Ines Breuksch; Teresa Laguna; Cornelia Dietrich; Susanne Strand; Günter Schneider; Bernd Groner; Falk Butter; Thorsten Heinzel; Walburgis Brenner; et al. (Archives of Toxicology, 2018)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

A first report on coexistence and hybridization of Mytilus trossulus and M. edulis mussels in Greenland - R. Wenne; L. Bach; M. Zbawicka; J. Strand; J. H. McDonald (Polar Biology, 2016)

Development and testing of a prototype tool for integrated assessment of chemical status in marine environments - Jesper H. Andersen; Ciarán Murray; Martin M. Larsen; Norman Green; Tore Høgåsen; Elin Dahlgren; Galina Garnaga-Budrė; Kim Gustavson; Michael Haarich; Emilie M.F. Kallenbach; Jaakko Mannio; Jakob Strand; et al. (Environmental Monitoring and Assessment, 2016)

Analyses of historical and current populations of black grouse in Central Europe reveal strong effects of genetic drift and loss of genetic diversity - Gernot Segelbacher; Tanja M. Strand; María Quintela; Tomas Axelsson; Hugh A. H. Jansman; Hans-Peter Koelewijn; Jacob Höglund (Conservation Genetics, 2014)

Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women - S. Ellefsen; O. Vikmoen; G. Slettaløkken; J. E. Whist; H. Nygaard; I. Hollan; I. Rauk; G. Vegge; T. A. Strand; T. Raastad; B. R. Rønnestad (European Journal of Applied Physiology, 2014)

Seasonal variation in mineralization rates (C-N-P-Si) of mussel Mytilus edulis biodeposits - H. M. Jansen; M. C. J. Verdegem; Ø. Strand; A. C. Smaal (Marine Biology, 2012)

The Arctic Coastal Dynamics Database: A New Classification Scheme and Statistics on Arctic Permafrost Coastlines - Hugues Lantuit; Pier Paul Overduin; Nicole Couture; Sebastian Wetterich; Felix Aré; David Atkinson; Jerry Brown; Georgy Cherkashov; Dmitry Drozdov; Donald Lawrence Forbes; Allison Graves-Gaylord; Mikhail Grigoriev; et al. (Estuaries and Coasts, 2012)

Voluntary responses and limits of tolerance to pressure reduction and swimbladder expansion in farmed Atlantic cod - Tore S. Kristiansen; Lars H. Stien; Jan Erik Fosseidengen; Espen Strand; Jon-Erik Juell (Aquaculture International, 2011)

Seaward migrating Atlantic salmon smolts with low levels of gill Na+, K+ -ATPase activity; is sea entry delayed? - Jo E. T. Strand; Jan G. Davidsen; Even H. Jørgensen; Andun H. Rikardsen (Environmental Biology of Fishes, 2011)

Fine root dynamics in a loblolly pine forest are influenced by free‐air‐CO 2 ‐enrichment: a six‐year‐minirhizotron study - SETH G. PRITCHARD; ALLAN E. STRAND; M. LUKE McCORMACK; MICHEAL A. DAVIS; ADRIEN C. FINZI; ROBERT B. JACKSON; ROSER MATAMALA; HUGO H. ROGERS; RAM OREN (Global Change Biology, 2008)
Efforts to characterize carbon (C) cycling among atmosphere, forest canopy, and soil C pools are hindered by poorly quantified fine root dynamics. We characterized the influence of free‐air‐CO 2 ‐enrichment (ambient +200 ppm) on fine roots for a period of 6 years (Autumn 1998 through Autumn 2004) in an 18‐year‐old loblolly pine ( Pinus taeda ) plantation near Durham, NC, USA using minirhizotrons. Root production and mortality were synchronous processes that peaked most years during spring and early summer. Seasonality of fine root production and mortality was not influenced by atmospheric CO 2 availability. Averaged over all 6 years of the study, CO 2 enrichment increased average fine root standing crop (+23%), annual root length production (+25%), and annual root length mortality (+36%). Larger increase in mortality compared with production with CO 2 enrichment is explained by shorter average fine root lifespans in elevated plots (500 days) compared with controls (574 days). The effects of CO 2 ‐enrichment on fine root proliferation tended to shift from shallow (0–15 cm) to deeper soil depths (15–30) with increasing duration of the study. Diameters of fine roots were initially increased by CO 2 ‐enrichment but this effect diminished over time. Averaged over 6 years, annual fine root NPP was estimated to be 163 g dw m −2 yr −1 in CO 2 ‐enriched plots and 130 g dw m −2 yr −1 in control plots ( P = 0.13) corresponding to an average annual additional input of fine root biomass to soil of 33 g m −2 yr −1 in CO 2 ‐enriched plots. A lack of consistent CO 2 × year effects suggest that the positive effects of CO 2 enrichment on fine root growth persisted 6 years following minirhizotron tube installation (8 years following initiation of the CO 2 fumigation). Although CO 2 ‐enrichment contributed to extra flow of C into soil in this experiment, the magnitude of the effect was small suggesting only modest potential for fine root processes to directly contribute to soil C storage in south‐eastern pine forests.

Population structure in a critically endangered arctic fox population: does genetics matter? - L. DALÉN; K. KVALØY; J. D. C. LINNELL; B. ELMHAGEN; O. STRAND; M. TANNERFELDT; H. HENTTONEN; E. FUGLEI; A. LANDA; A. ANGERBJÖRN (Molecular Ecology, 2006)
The arctic fox ( Alopex lagopus ) in Scandinavia is classified as critically endangered after having gone through a severe decline in population size in the beginning of the 20th century, from which it has failed to recover despite more than 65 years of protection. Arctic foxes have a high dispersal rate and often disperse over long distances, suggesting that there was probably little population differentiation within Scandinavia prior to the bottleneck. It is, however, possible that the recent decline in population size has led to a decrease in dispersal and an increase in population fragmentation. To examine this, we used 10 microsatellite loci to analyse genetic variation in 150 arctic foxes from Scandinavia and Russia. The results showed that the arctic fox in Scandinavia presently is subdivided into four populations, and that the Kola Peninsula and northwest Russia together form a large fifth population. Current dispersal between the populations seemed to be very low, but genetic variation within them was relatively high. This and the relative F ST values among the populations are consistent with a model of recent fragmentation within Scandinavia. Since the amount of genetic variation is high within the populations, but the populations are small and isolated, demographic stochasticity seems to pose a higher threat to the populations’ persistence than inbreeding depression and low genetic variation.

Surrogate Pheromone Plumes in Three Forest Trunk Spaces: Composite Statistics and Case Studies - Harold W. Thistle; Holly Peterson; Gene Allwine; Brian Lamb; Tara Strand; Edward H. Holsten; Patrick J. Shea (Forest Science, 2004)
An atmospheric tracer gas was used as a pheromone surrogate to study near-field canopy dispersion within the trunk space. The objective is to improve guidance for forest managers deploying bark beetle antiaggregation pheromone sources to protect high-value forest stands. Data are shownfrom field studies in three forest canopies (oak-hickory, Quercus-Carya; lodgepole pine, Pinus contorta Dougl. ex Loud.; and ponderosa pine, Pinus ponderosa Dougl. ex Laws.) and include over 13,000 chemical tracer samples compiled into half-hour dispersion fields arounda point source. Maximum normalized concentrations (χ/Q) at each arc distance for each sampling period were of similar order at 5 m from the tracer source in the three canopies, although the differences in maximum χ/Q between canopies increased with distance from thesource. Plume dilution was highest in this study in the more open ponderosa pine canopy. A high-frequency tracer gas analyzer was also deployed to ascertain the structure of the gas plumes at 1 Hz. The high-frequency tracer data showed that the 30-minute average mean plumes are compositesof narrow filamentous plumes. The near-field plumes in each canopy were strongly affected by changes in atmospheric stability, as wander range and meander frequency increased after the morning transition to an unstable boundary layer. FOR. SCI. 50(5):610–625.

Analysis and comparison of the microbial community structures of two enrichment cultures capable of reductively dechlorinating TCE and cis ‐DCE - April Z. Gu; Brian P. Hedlund; James T. Staley; Stuart E. Strand; H. David Stensel (Environmental Microbiology, 2004)
Summary In order to study the effect of different chloroethenes (electron acceptors) on the bacterial composition of dechlorinating communities, two reductive dechlorinating enrichment cultures were developed that were able to reduce trichloroethene (TCE) and cis ‐1,2‐dichloroethene ( cis ‐DCE) to ethene using hydrogen as electron donor, respectively. The inoculum for the cultures was material from a methanogenic fluidized bed reactor (FBR), which was originally seeded with digester sludge and showed a stable capacity for tetrachloroethene (PCE) reduction to ethene for over six years. Molecular methods were used to determine and compare the microbial communities of these two enrichment cultures. A clone library of bacterial 16S rRNA genes was generated for each enrichment. The clones were screened into different groups by restriction fragment length polymorphism (RFLP) analysis using two different four base pair recognition restriction enzymes. A total of 12 sequence types were identified by phylogenetic analysis of nearly complete 16S rDNA sequences (∼1450 bp). The sequences were affiliated with six recognized phyla of the domain Bacteria: Firmicutes (low G+C Gram‐positives), Chloroflexi (green non‐sulphur bacteria), Actinobacteria (high G+C Gram‐positives), Bacteroidetes (Cytophaga‐Flexibacter‐Bacteroides), Nitrospira and Spirochaetes. The results led to the identification of an organism closely related to Dehalococcoides ethenogenes to be the presumptive dechlorinator in both enrichments. Different electron acceptors affected the bacterial diversity and the community profiles of the two enrichments. Most of the sequences identified in our dechlorinating enrichments shared high similarities with sequences previously obtained from other enriched dechlorinating cultures and chlorinated‐compound‐contaminated sediments or aquifers, suggesting these bacteria may have direct or indirect roles in reductive dechlorination.

Integrating biodiversity priorities with conflicting socio-economic values in the Guinean–Congolian forest region - P.H. Williams; J.L. Moore; A. Kamden Toham; T.M. Brooks; H. Strand; J. D'Amico; M. Wisz; N.D. Burgess; A. Balmford; C. Rahbek (Biodiversity and Conservation, 2003)

High‐resolution determination of coral reef bottom cover from multispectral fluorescence laser line scan imagery - Charles H. Mazel; Michael P. Strand; Michael P. Lesser; Michael P. Crosby; Bryan Coles; Andrew J. Nevis (Limnology and Oceanography, 2003)
A prototype in‐water laser line‐scanning multispectral fluorescence imaging system was evaluated for its ability to provide data that could be used to determine the quantitative distribution and abundance of various functional groups on coral reefs. The system collected fluorescence imagery in three spectral bands with 1 cm 2 resolution at sites in Florida and the Bahamas. Fluorescence excitation was at 488 nm, and imagery was collected in emission bands centered at 520, 580, and 685 nm. Ground truth data on bottom cover was collected by divers using conventional line transect and photographic quadrat methods. A set of classification rules based on the relative signal levels in the three fluorescence channels was developed to assign the image pixels to functional groups. Once the image was classified, percent cover data for the groups were computed for the full image and for subsets of the image chosen to simulate line transect, grid survey, and photographic quadrat surveys. The statistics of percent cover of various bottom types derived from the fluorescence image compared favorably with those determined by diver survey techniques. The results demonstrate that fluorescence imaging has the long‐term potential to provide coverage of large spatial areas of coral reefs at high resolution, with automated classification and quantification of functional groups in the image.

Testicular atrophy and loss of nerve growth factor-immunoreactive germ cell line in rats exposed to n-hexane and a protective effect of simultaneous exposure to toluene or xylene - Per Nyln; Ted Ebendal; Maria Eriksdotter-Nilsson; Tiiu Hansson; Andreas Henschen; Ann-Christin Johnson; Tony Kronevi; Ulrik Kvist; Nils O. Sjstrand; Gunnar Hglund; Lars Olson (Archives of Toxicology, 1989)

Superparasitism and ovicide in parasitic Hymenoptera: theory and a case study of the ectoparasitoid Bracon hebetor - M. R. Strand; H. C. J. Godfray (Behavioral Ecology and Sociobiology, 1989)

Sectional notes - Carl H. Metzger; W. B. Ward; H. L. Cochran; J. B. R. Dickey; A. B. Strand; W. H. Friend; H. H. Zimmerley; G. S. Ralston (American Journal of Potato Research, 1939)